Preparation method and application of composite material for extracting low-impurity uranium from seawater

By preparing CMOS@NSF composites, the problem of low impurity uranium extraction efficiency in seawater is solved, and efficient and stable uranium capture and extraction effects are achieved.

CN119707045APending Publication Date: 2025-03-28SOUTHWEAT UNIV OF SCI & TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510077154.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively extract low-impact uranium from seawater, especially when uranium concentration is low and there are multiple competitive ions in seawater.

Method used

By preparing a composite material CMOS@NSF, ammonium molybdate tetrahydrate and cobalt sulfate heptahydrate as raw materials, after multiple crystallization and hydrothermal reactions, a sulfated polyoxymetallic acid with high capture ability was formed to grow in situ on Ni2S3.

Benefits of technology

The CMOS@NSF composite material has efficient capture ability of uranium in seawater in self-assembly device, with an extraction rate of 86.67%, and an extraction capacity of 2.65 mg/g per day. The U(VI) extraction rate in simulated electrochemical uranium extraction experiment reached 90%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707045A_ABST
    Figure CN119707045A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a composite material for extracting low-impurity uranium from seawater, and the preparation method comprises the following steps: dissolving ammonium molybdate tetrahydrate in boiling water, and then pouring a cobaltous sulfate heptahydrate solution into the boiling solution; then adding H2O2 while stirring, and continuously boiling; performing low-temperature cold crystallization on the obtained product, and performing low-temperature crystallization on the obtained crystal twice in water to obtain relatively pure CoMo6; the preparation method comprises the following steps: adding CoMo6 into deionized water, then adding thiourea and stirring, then carrying out hydrothermal reaction on the CoMo6 and foamed nickel treated by hydrochloric acid in a reaction kettle, washing the obtained material by using deionized water and ethanol after the hydrothermal reaction is completed, and then drying to obtain the CMOS (at) NSF composite material. According to the present invention, the prepared CMOS (at) NSF composite material has strong UO2 < 2 + > capturing ability, and can effectively capture uranium in seawater, the U (VI) extraction rate of the true seawater uranium by using the CMOS (at) NSF composite material in the self-assembly device reaches 86.67%, and the extraction ability is 2.65 mg / g per day.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of organic matter, conventional metal and radioactive wastewater treatment, uranium extraction from seawater and environmental protection. More specifically, the present invention relates to a preparation method and application of a composite material for extracting low-impurity uranium from seawater. Background Art

[0002] As an important raw material and strategic material for the nuclear industry, uranium plays an increasingly important role in today's world where traditional fossil fuels are increasingly depleted and energy demand is rising. With the development of society and economy, the development and utilization of nuclear energy consumes a large amount of uranium resources. It is expected that in less than a century, these uranium resources will be exhausted in terrestrial ores, and uranium will be in short supply. Therefore, alternative uranium resources must be found. The total amount of uranium resources in seawater is estimated to be 4.5 billion tons, which is 1,000 times the uranium resources on land. The development of uranium extraction from seawater is of great strategic significance for ensuring the sustainable development of nuclear energy and promoting the comprehensive utilization of marine resources. However, there are many challenges in extracting uranium from seawater, such as ultra-low uranium concentration, competition with coexisting ions, complex marine environment, biological contamination problems and limitations of adsorbent materials.

[0003] Electrochemical extraction of uranium using electroreduction of uranium(VI) has attracted increasing attention due to the enhanced extraction capacity caused by crystallization of the final uranium product, enhanced kinetics driven by electric fields, and increased resistance to non-reducing interfering ions. In the electrochemical extraction of uranium, the extraction efficiency is mainly determined by the electrode materials, which has prompted researchers to focus on the design of electrode materials. However, in the existing research reports to date, the electrode materials of the electrochemically extracted uranium products are either composed of alkali metals or deposited in unstable mixed valence states. The use of electrochemical methods for the reduction of U(VI) to U(IV) in seawater, especially with UO, has not been reported in the literature. 2 in the form of. Summary of the invention

[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0005] In order to achieve these purposes and other advantages according to the present invention, a method for preparing a composite material for extracting low-impurity uranium from seawater is provided, comprising the following steps:

[0006] Step 1: Dissolve ammonium molybdate tetrahydrate in boiling water, then pour cobalt sulfate heptahydrate solution into the boiling solution; then add H 2 O 2 , and continue to boil;

[0007] Step 2: Cool the product of step 1 to make it crystallize, and then crystallize the obtained crystals twice in water to obtain relatively pure (NH4) 3 [CoMo 6 O 24 H 6 ]·7H 2 O (hereinafter referred to as CoMo 6 );

[0008] Step 3: CoMo 6 Add deionized water, then add thiourea and stir, then put it together with the nickel foam treated with hydrochloric acid into a polytetrafluoroethylene-lined reactor for hydrothermal reaction. After the reaction is completed, rinse the resulting material with deionized water and ethanol, and then dry to obtain a composite material for extracting low-impurity uranium from seawater, namely, CMOS@NSF composite material.

[0009] Preferably, in step 1, ammonium molybdate tetrahydrate, cobalt sulfate heptahydrate, boiling water and H 2 O 2 The mass volume ratio is 30-32 g:4-5 g:200-300 mL:1-5 mL, and boiling is continued for 30 min.

[0010] Preferably, in step 2, the temperature of the low-temperature cooling crystallization is 5-8°C.

[0011] Preferably, in step 3, thiourea and CoMo 6 When adding, the atomic ratio of S:Mo is 4:1 to 1:2. 6 The mass ratio of nickel to deionized water is 1:300-400, and the size of the nickel foam is 2×2 cm.

[0012] Preferably, in step three, the stirring time is 15 to 30 minutes, the hydrothermal reaction temperature is 180 to 200° C., and the reaction time is 8 hours.

[0013] Preferably, before adding the nickel foam in step 3, the nickel foam is pretreated by:

[0014] S1. Ultrasonic treatment of nickel foam in hydrochloric acid solution, ethanol and deionized water to remove oxides and grease on the surface, and then drying in a constant temperature drying oven;

[0015] S2, using nickel foam as the working electrode, graphite plate as the counter electrode, and iron ion solution as the electroplating solution, using electrodeposition to uniformly deposit iron on the surface of nickel foam, followed by high-temperature calcination to form a nickel-iron alloy on the surface;

[0016] S3, acid-leaching the nickel-iron alloy to remove iron in the nickel-iron alloy, and then washing it with deionized water to obtain pretreated nickel foam.

[0017] Preferably, in S1, the ultrasonic frequency is 30-40 kHz, the ultrasonic treatment time is 10-30 min, the drying temperature is 100-130° C., and the drying time is 5-10 min.

[0018] Preferably, in S2, the iron ion solution is one or more of a ferric chloride solution and a ferric sulfate solution, the concentration of the iron ion solution is 0.01 to 1 M in terms of iron ions, the electrodeposition voltage is -0.1 to -0.8 V, and the electrodeposition amount is 3 C / cm 2 ~100C / cm 2 The calcination temperature is 1400-1600°C, and the calcination time is 2-4h.

[0019] Preferably, in S3, hydrochloric acid is used for acid leaching, the concentration of the hydrochloric acid is 50-70wt%, and the acid leaching time is 2-6h.

[0020] The present invention also provides an application of a CMOS@NSF composite material, characterized in that the CMOS@NSF composite material is used for electrochemical reduction extraction of low-impurity uranium from seawater.

[0021] Beneficial effect: The present invention uses sulfide polyoxymetallate (NH4) 3 [CoMo 6 O 24 H 6 ]·7H 2 O in Ni 2 S 3 The CMOS@NSF composite material was prepared by in-situ growth on UO 2 2+ It has a strong capture ability and can effectively capture uranium in seawater. The U(VI) extraction rate of CMOS@NSF composite material in real seawater uranium in a self-assembled device reaches 86.67%, and the extraction capacity is 2.65 mg / g per day. In the simulated electrochemical uranium extraction experiment, the U(VI) extraction rate of 180 minutes reaches 90%. The present invention also pre-treats the nickel foam. During the pre-treatment, the mutual solubility of nickel and iron is utilized. Iron is uniformly deposited on the porous surface of the nickel foam by electrodeposition. Then, calcination is used to promote the mutual solubility of nickel and iron to form an alloy layer on the surface of the porous nickel. The alloy layer is formed in situ on the porous morphological surface of the original nickel foam. Acid leaching is then used to selectively remove iron in the alloy, and a microporous structure is formed in situ on the porous surface structure of the original nickel foam to roughen the surface structure, which helps to increase the reaction rate of thiourea and nickel foam during the subsequent hydrothermal reaction and generate more Ni 2 S 3 , which in turn helps more CoMo6 In situ generation of Ni 2 S 3 In order to improve the uranium extraction performance of the final prepared material.

[0022] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM image of the CMOS@NSF composite material prepared in Example 1;

[0024] Figure 2 HRTEM image of the CMOS@NSF composite material prepared in Example 1 (the inset shows the enlarged view and the corresponding lattice fringes);

[0025] Figure 3 HRTEM image of the amorphous region on the surface of the CMOS@NSF composite material prepared in Example 1 (the inset is the corresponding SAED pattern);

[0026] Figure 4 The STEM-EDS element mapping diagram of Co, Mo, Ni, O and S of the CMOS@NSF composite material prepared in Example 1;

[0027] Figure 5 is the X-ray diffraction pattern of the CMOS@NSF composite material prepared in Example 1;

[0028] Figure 6 is the EPR spectrum of the CMOS@NSF composite material prepared in Example 1;

[0029] Figure 7 The formation mechanism diagram of the CMOS@NSF composite material prepared in Example 1;

[0030] Figure 8 The LSV curve of the electrode for electrochemically extracting uranium from a mixed solution of 500 mg / LU and 0.5 M sodium sulfate in Application Example 1;

[0031] Fig. 9 is a graph showing the relationship between the electrochemical uranium extraction time and the extraction rate in Application Example 1;

[0032] Fig.10 is a graph showing the relationship between the electrochemical uranium extraction time and the extraction rate in Application Example 2;

[0033] Fig.11 A physical picture of the simple electrochemical uranium extraction device from seawater assembled for Application Example 2;

[0034] Fig.12For CMOS@NSF, add 100mg L -1 Graph of extraction efficiency of uranium in seawater for repeated use;

[0035] Fig.13 This is a SEM image of the CMOS@NSF composite material prepared in Example 2;

[0036] Fig.14 This is a SEM image of the CMOS@NSF composite material prepared in Example 3;

[0037] Fig.15 This is a SEM image of the CMOS@NSF composite material prepared in Example 4;

[0038] Fig.16 This is the SEM image of the CMOS@NSF composite material prepared in Example 5. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0040] Example 1

[0041] A method for preparing a composite material for extracting low-impurity uranium from seawater, characterized in that it comprises the following steps:

[0042] Step 1: Dissolve 30.9 g of ammonium molybdate tetrahydrate in 260 mL of boiling water, then pour 30 mL of an aqueous solution containing 4.2 g of cobalt sulfate heptahydrate into the boiling solution; then add 2 mL of H 2 O 2 , and continue boiling for 30 minutes;

[0043] Step 2: The product of step 1 is cooled to crystallize, and the obtained crystals are crystallized twice in water at low temperature to obtain relatively pure CoMo 6 ;

[0044] Step 3: 0.06g CoMo 6 Add 20 mL of deionized water, then add 0.045 g of thiourea and stir for 15 min (corresponding to S:Mo is 2:1). Then put it together with the nickel foam (2×2 cm) treated with hydrochloric acid into a polytetrafluoroethylene-lined stainless steel high-pressure reactor and carry out hydrothermal reaction at 180°C for 8 h. After the reaction is completed, the obtained material is rinsed with deionized water and ethanol, and then dried to obtain a CMOS@NSF composite material.

[0045] Figure 1This is the SEM image of the CMOS@NSF composite material prepared in Example 1 (the inset shows a magnified view of the tip). It can be seen that the material is composed of needle-like structures with a rough surface and a diameter of 100 nm, forming the overall structure of a sea urchin.

[0046] Figure 2 HRTEM image of the CMOS@NSF composite material prepared in Example 1 (the inset shows the enlarged view and the corresponding lattice fringes). It can be seen that the lattice fringes with plane spacing of 0.179 nm and 0.284 nm correspond to Ni 3 S 2 The (211) and (110) facets, except for the well-defined Ni 3 S 2 Outside the core, an amorphous shell structure was also observed.

[0047] Figure 3 HRTEM image of the amorphous region on the surface of the CMOS@NSF composite material prepared in Example 1 (the inset is the corresponding SAED pattern), further confirming the amorphous structure of the surface.

[0048] Figure 4 This is the STEM-EDS element mapping diagram of Co, Mo, Ni, O and S of the CMOS@NSF composite material prepared in Example 1. It can be seen that the elements Co, Mo, Ni, O and S are evenly distributed on the surface of the material.

[0049] Figure 5 This is the X-ray diffraction pattern of the CMOS@NSF composite material prepared in Example 1. It can be seen from the figure that two groups of characteristic peaks are identified, namely standard metal Ni and hexagonal Ni 3 S 2 .

[0050] Figure 6 This is the EPR spectrum of the CMOS@NSF composite material prepared in Example 1. It can be seen from the figure that the resonant magnetic field signal of CMOS@NSF is significantly stronger than that of CoMo 6 , which is due to the presence of a large number of lone pairs of electrons on the low-coordinated oxygen atoms.

[0051] Figure 7 The formation mechanism diagram of the CMOS@NSF composite material prepared in Example 1. It can be seen from the figure that in CoMo 6 During the sulfurization process, the coordinated O atoms around the Co center and the bridging O atoms between the Mo atoms are sulfurized. In addition, the retained external O atoms connected to the Mo atoms become unsaturated due to the incorporation of the less electronegative S atoms, resulting in the formation of terminal O atoms at the periphery.

[0052] Example 2

[0053] A method for preparing a composite material for extracting low-impurity uranium from seawater, characterized in that it comprises the following steps:

[0054] Step 1: Dissolve 30.9 g of ammonium molybdate tetrahydrate in 260 mL of boiling water, then pour 30 mL of an aqueous solution containing 4.2 g of cobalt sulfate heptahydrate into the boiling solution; then add 2 mL of H 2 O 2 , and continue boiling for 30 minutes;

[0055] Step 2: The product of step 1 is cooled to crystallize, and the obtained crystals are crystallized twice in water at low temperature to obtain relatively pure CoMo 6 ;

[0056] Step 3: 0.12g CoMo 6 20 mL of deionized water was added, followed by 0.045 g (corresponding to S:Mo ratio of 1:2) of thiourea and stirred for 15 min. Then, it was placed together with nickel foam (2×2 cm) treated with hydrochloric acid in a polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction at 180 °C for 8 h. After the reaction was completed, the obtained material was rinsed with deionized water and ethanol, and then dried to obtain a CMOS@NSF composite material. Fig.13 This is the SEM image of the CMOS@NSF composite material prepared in Example 2.

[0057] Example 3

[0058] A method for preparing a composite material for extracting low-impurity uranium from seawater, characterized in that it comprises the following steps:

[0059] Step 1: Dissolve 30.9 g of ammonium molybdate tetrahydrate in 260 mL of boiling water, then pour 30 mL of an aqueous solution containing 4.2 g of cobalt sulfate heptahydrate into the boiling solution; then add 2 mL of H 2 O 2 , and continue boiling for 30 minutes;

[0060] Step 2: The product of step 1 is cooled to crystallize, and the obtained crystals are crystallized twice in water at low temperature to obtain relatively pure CoMo 6 ;

[0061] Step 3: 0.06g CoMo 620 mL of deionized water was added, followed by 0.0225 g (corresponding to S:Mo ratio of 1:1) of thiourea and stirred for 15 min. Then, it was placed together with nickel foam (2×2 cm) treated with hydrochloric acid in a polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction at 180 °C for 8 h. After the reaction was completed, the obtained material was rinsed with deionized water and ethanol, and then dried to obtain a CMOS@NSF composite material. Fig.14 This is the SEM image of the CMOS@NSF composite material prepared in Example 3.

[0062] Example 4

[0063] A method for preparing a composite material for extracting low-impurity uranium from seawater, characterized in that it comprises the following steps:

[0064] Step 1: Dissolve 30.9 g of ammonium molybdate tetrahydrate in 260 mL of boiling water, then pour 30 mL of an aqueous solution containing 4.2 g of cobalt sulfate heptahydrate into the boiling solution; then add 2 mL of H 2 O 2 , and continue boiling for 30 minutes;

[0065] Step 2: The product of step 1 is cooled to crystallize, and the obtained crystals are crystallized twice in water at low temperature to obtain relatively pure CoMo 6 ;

[0066] Step 3: 0.06g CoMo 6 20 mL of deionized water was added, followed by 0.0675 g (corresponding to S:Mo ratio of 3:1) of thiourea and stirred for 15 min. Then, it was placed together with nickel foam (2×2 cm) treated with hydrochloric acid in a polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction at 180 °C for 8 h. After the reaction was completed, the obtained material was rinsed with deionized water and ethanol, and then dried to obtain a CMOS@NSF composite material. Fig.15 This is the SEM image of the CMOS@NSF composite material prepared in Example 4.

[0067] Example 5

[0068] A method for preparing a composite material for extracting low-impurity uranium from seawater, characterized in that it comprises the following steps:

[0069] Step 1: Dissolve 30.9 g of ammonium molybdate tetrahydrate in 260 mL of boiling water, then pour 30 mL of an aqueous solution containing 4.2 g of cobalt sulfate heptahydrate into the boiling solution; then add 2 mL of H 2 O 2 , and continue boiling for 30 minutes;

[0070] Step 2: The product of step 1 is cooled to crystallize, and the obtained crystals are crystallized twice in water at low temperature to obtain relatively pure CoMo 6 ;

[0071] Step 3: 0.06g CoMo 6 Add 20 mL of deionized water, then add 0.09 g (corresponding to S:Mo ratio of 4:1) of thiourea and stir for 15 min. Then put it together with nickel foam (2×2 cm) treated with hydrochloric acid into a stainless steel autoclave lined with polytetrafluoroethylene and perform hydrothermal reaction at 180 ° C for 8 h. After the reaction is completed, rinse the obtained material with deionized water and ethanol, and then dry it to obtain a CMOS@NSF composite material. Fig.16 This is the SEM image of the CMOS@NSF composite material prepared in Example 5.

[0072] Example 6

[0073] A method for preparing a composite material for extracting low-impurity uranium from seawater, characterized in that it comprises the following steps:

[0074] Step 1: Dissolve 30.9 g of ammonium molybdate tetrahydrate in 260 mL of boiling water, then pour 30 mL of an aqueous solution containing 4.2 g of cobalt sulfate heptahydrate into the boiling solution; then add 2 mL of H 2 O 2 , and continue boiling for 30 minutes;

[0075] Step 2: The product of step 1 is cooled to crystallize, and the obtained crystals are crystallized twice in water at low temperature to obtain relatively pure CoMo 6 ;

[0076] Before adding nickel foam in step 3, the nickel foam is pretreated as follows:

[0077] S1. The nickel foam was ultrasonically treated in hydrochloric acid solution, ethanol and deionized water respectively, with the ultrasonic frequency of 30kHz and the ultrasonic treatment time of 20min to remove oxides and grease on the surface, and then dried in a constant temperature drying oven;

[0078] S2, using nickel foam as the working electrode, graphite plate as the counter electrode, and 0.25M ferric chloride solution as the electroplating solution, electroplating was used to uniformly deposit iron on the surface of nickel foam, the electroplating voltage was -0.5V, and the electroplating amount was 15C / cm 2 After iron is deposited on the surface, the nickel foam is calcined at 1400°C for 2.5h to form a nickel-iron alloy on its surface;

[0079] S3, the nickel foam with nickel-iron alloy formed on the surface is acid-leached with hydrochloric acid, the concentration of the hydrochloric acid is 70wt%, the acid-leaching time is 2h, the iron is removed, and then it is washed with deionized water to obtain pretreated nickel foam.

[0080] Step 3: 0.06g CoMo 6 Add 20 mL of deionized water, then add 0.045 g of thiourea and stir for 15 min. Then put it together with the pretreated nickel foam (2×2 cm) into a stainless steel high-pressure reactor lined with polytetrafluoroethylene and carry out hydrothermal reaction at 180°C for 8 h. After the reaction is completed, the obtained material is rinsed with deionized water and ethanol, and then dried to obtain a CMOS@NSF composite material.

[0081] Comparative Example 1

[0082] Step 1: Dissolve 30.9 g of ammonium molybdate tetrahydrate in 260 mL of boiling water, then pour 30 mL of an aqueous solution containing 4.2 g of cobalt sulfate heptahydrate into the boiling solution; then add 2 mL of H 2 O 2 , and continue boiling for 30 minutes;

[0083] Step 2: The product of step 1 is cooled to crystallize, and the obtained crystals are crystallized twice in water at low temperature to obtain relatively pure CoMo 6 .

[0084] Comparative Example 2

[0085] 0.045 g of thiourea was added to 20 mL of deionized water and stirred for 15 min. Then, it was placed in a polytetrafluoroethylene-lined stainless steel autoclave together with nickel foam (2×2 cm) treated with hydrochloric acid, and a hydrothermal reaction was carried out at 180 ° C for 8 h. After the reaction was completed, the obtained material was rinsed with deionized water and ethanol, and then dried to obtain Ni 2 S 3 / nickel foam composite material.

[0086] Comparative Example 3

[0087] The difference between this comparative example and Example 6 is that S3 is not performed, and the rest is consistent with Example 6.

[0088] Comparative Example 4

[0089] The difference between this comparative example and Example 6 is that S2 and S3 are not performed, and the rest are consistent with Example 6.

[0090] Application Example 1

[0091] The materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were respectively used for electrochemical uranium extraction test, and the electrochemical test was performed using a CHI660E electrochemical workstation. The materials prepared in Example 1 and Comparative Example 1 were cut into small pieces of 1×2 cm and directly used as working electrodes, while the materials prepared in Comparative Example 2 were weighed 5 mg CoMo 6 , dispersed in 2mL of ethanol, then 35μL of Nafion solution was added, and this mixture was brushed on a 1×2cm carbon felt (CF) as a working electrode, and then tested using a three-electrode system with an Ag / AgCl electrode as a reference electrode and a platinum wire electrode as a counter electrode. Electrochemical uranium extraction was carried out in a mixed solution of 500mg / LU and 0.5M sodium sulfate. The concentrations of uranium and other cations in the solution after electrochemical extraction were determined by the ICP method. During the desorption process, the uranium-loaded working electrode was analyzed at a reverse voltage of 1.4V in 0.5M sodium sulfate for 10 minutes. The extraction experiment was repeated 3 times.

[0092] Application Example 2

[0093] The materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were respectively used to carry out electrochemical uranium extraction tests in real seawater. Fig.11 The simple electrochemical uranium extraction device shown in the figure was used to electrochemically extract uranium from real seawater under existing laboratory conditions. The electrochemical test was performed using a CHI660E electrochemical workstation. The materials prepared in Example 1 and Comparative Example 1 were cut into small pieces of 3×3 cm and directly used as working electrodes, while Comparative Example 2 was made by weighing 5 mg CoMo 6 , dispersed in 2mL of ethanol, and then 35μL of Nafion solution was added. This mixture was brushed on a 3×3cm carbon felt (CF) as a working electrode. The three-electrode system was used for testing, with an Ag / AgCl electrode as the reference electrode and a platinum wire electrode as the counter electrode. Electrochemical uranium extraction was performed in real seawater that was pre-filtered using a filtration system. After 24 hours of electrochemical uranium extraction, the electrode material was removed, rinsed with pure water, and then soaked in 0.5M hydrochloric acid to elute the extracted uranium. The solution was then prepared into a 10mL concentrated solution. The uranium content in the eluted solution was determined by the ICP method, and its extraction capacity was calculated. The CMOS@NSF material extracted 71.55μg of uranium from 25L of seawater, equivalent to an extraction capacity of 2.65mg / g per day, and the U(VI) extraction rate reached 86.67%.

[0094] Figure 8 LSV curve of the electrode for electrochemical uranium extraction in Application Example 1; As can be seen from the figure, CMOS@NSF shows a lower negative peak potential (-0.65V) than Ni 3 S 2 / Foam Nickel (-0.83V) and CoMo 6 In addition, a new reduction peak appears at -1.32 V in the LSV curve of CMOS@NSF, corresponding to the reduction of U(V) to U(IV), indicating that CMOS@NSF has a strong electrochemical reduction ability for U(VI).

[0095] Fig. 9 Figure 1 is the relationship between the electrochemical uranium extraction time and the extraction rate of application example 1. It can be seen from the figure that after 180 minutes of electrochemical uranium extraction, the U(VI) extraction rate of CMOS@NSF is 90% (no saturation is observed), which is significantly higher than that of Ni 3 S 2 / Foam nickel (63.7%) and CoMo 6 (40.2%).

[0096] Fig.10 The figure shows the relationship between the electrochemical uranium extraction time and the extraction rate of application example 1 and comparative examples 1 and 2. It can be seen from the figure that the electrochemical extraction rate of the CMOS@NSF material prepared by the present invention is significantly better than that of CoMo in the same time. 6 and Ni 2 S 3 / Nickel foam.

[0097] Application Example 3

[0098] The materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were respectively used for electrochemical uranium extraction test, and the electrochemical test was performed using a CHI660E electrochemical workstation. The materials prepared in Example 1 and Comparative Example 1 were cut into small pieces of 1×2 cm and directly used as working electrodes, while the materials prepared in Comparative Example 2 were weighed 5 mg CoMo 6 , dispersed in 2mL ethanol, then added 35μL Nafion solution, brushed this mixture on 1×2cm carbon felt (CF) as the working electrode, and then tested using a three-electrode system, with Ag / AgCl electrode as the reference electrode and platinum wire electrode as the counter electrode. Electrochemical uranium extraction was carried out in 100mg / LU seawater. The concentrations of uranium and other cations in the solution after electrochemical extraction were determined by ICP method. After uranium extraction was completed, desorption was performed, and then the adsorption and desorption experiment was repeated in 100mg / LU seawater using the same electrode, and repeated 9 times.

[0099] Fig.12 For CMOS@NSF, add 100mg L -1The extraction rate of uranium reused in seawater. It can be seen from the figure that after 9 cycles of elution and reuse of the same electrode, CMOS@NSF showed better cycle stability and the U(VI) extraction efficiency remained above 85%.

[0100] Application Example 4

[0101] The electrochemical uranium extraction test was carried out using the materials prepared in Example 6, Comparative Examples 3 and 4, and the electrochemical test was carried out using a CHI660E electrochemical workstation, wherein the material prepared in Example 5 was cut into small pieces of 1×2 cm and directly used as a working electrode, and then tested using a three-electrode system, with an Ag / AgCl electrode as a reference electrode and a platinum wire electrode as a counter electrode. Electrochemical uranium extraction was carried out in a mixed solution of 500 mg / LU and 0.5 M sodium sulfate. The concentrations of uranium and other cations in the solution after electrochemical extraction were determined by the ICP method.

[0102] After 180 minutes of electrochemical uranium extraction, it was found that the U(VI) extraction rate of CMOS@NSF prepared by pretreated nickel foam in Example 6 was 96.32%. During the pretreatment, the mutual solubility of nickel and iron was utilized, and iron was uniformly deposited on the porous surface of the nickel foam by electrodeposition. Then, calcination was used to promote the mutual solubility of nickel and iron to form an alloy layer on the surface of the porous nickel. The alloy layer was formed in situ on the porous morphological surface of the original nickel foam. Then, acid leaching was used to selectively remove iron from the alloy, and a microporous structure was formed in situ on the porous surface structure of the original nickel foam, so that the surface structure was roughened, which was helpful to improve the reaction rate of thiourea and nickel foam during the subsequent hydrothermal reaction and generate more Ni 2 S 3 , which in turn helps more CoMo 6 In situ generation of Ni 2 S 3 In order to improve the uranium extraction performance of the final prepared material. The U(VI) extraction rate of Comparative Example 3 is 75.24%, which is because the deposited iron is not removed, but affects the subsequent reaction rate, resulting in a poor uranium extraction rate of the final product; the U(VI) extraction rate of Comparative Example 4 is 91.02%, and Comparative Example 4 only further cleans the nickel foam, and the uranium extraction rate of the final product is improved less than that of Example 6.

[0103] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A method for preparing a composite material for extracting low-impurity uranium from seawater, characterized in that: The following steps are involved: Step 1: dissolve ammonium molybdate tetrahydrate in boiling water, then pour cobalt sulfate heptahydrate solution into the boiling solution; then add H2O2 while stirring and continue boiling; Step 2: The product of step 1 is cooled to crystallize, and the obtained crystals are crystallized twice in water at low temperature to obtain relatively pure (NH4)3[CoMo6O 24 H6]·7H2O; Step 3: (NH4)3[CoMo6O 24 H6]·7H2O is added into deionized water, and then thiourea is added and stirred. Then, it is put into a polytetrafluoroethylene-lined reactor together with the nickel foam treated with hydrochloric acid for hydrothermal reaction. After the reaction is completed, the obtained material is rinsed with deionized water and ethanol, and then dried to obtain a composite material for extracting low-impurity uranium from seawater, namely, CMOS@NSF composite material.

2. The method for preparing a composite material for extracting low-impurity uranium from seawater according to claim 1, characterized in that: In the step 1, the mass volume ratio of ammonium molybdate tetrahydrate, cobalt sulfate heptahydrate, boiling water and H2O2 is 30-32g:4-5g:200-300mL:1-5mL, and boiling is continued for 30min.

3. The method for preparing a composite material for extracting low-impurity uranium from seawater according to claim 1, characterized in that: In the step 2, the temperature of the low-temperature cooling crystallization is 5-8°C.

4. The method for preparing a composite material for extracting low-impurity uranium from seawater according to claim 1, characterized in that: In the step 3, thiourea and (NH4)3[CoMo6O 24 H6]·7H2O is added according to the atomic ratio of S:Mo of 4:1 to 1:2, (NH4)3[CoMo6O 24 The mass ratio of H6]·7H2O to deionized water is 1:300-400, and the size of the nickel foam is 2×2 cm.

5. The method for preparing a composite material for extracting low-impurity uranium from seawater according to claim 1, characterized in that: In the step 3, the stirring time is 15 to 30 minutes, the hydrothermal reaction temperature is 180 to 200° C., and the reaction time is 8 hours.

6. The method for preparing a composite material for extracting low-impurity uranium from seawater according to claim 1, characterized in that: Before adding nickel foam in step 3, the nickel foam is pretreated as follows: S1. Ultrasonic treatment of nickel foam in hydrochloric acid solution, ethanol and deionized water to remove oxides and grease on the surface, and then drying in a constant temperature drying oven; S2, using nickel foam as the working electrode, graphite plate as the counter electrode, and iron ion solution as the electroplating solution, using electrodeposition to uniformly deposit iron on the surface of nickel foam, followed by high-temperature calcination to form a nickel-iron alloy on the surface; S3, acid-leaching the nickel-iron alloy to remove iron in the nickel-iron alloy, and then washing it with deionized water to obtain pretreated nickel foam.

7. The method for preparing a composite material for extracting low-impurity uranium from seawater according to claim 6, characterized in that: In the S1, the ultrasonic frequency is 30-40 kHz, the ultrasonic treatment time is 10-30 min, the drying temperature is 100-130° C., and the drying time is 5-10 min.

8. The method for preparing a composite material for extracting low-impurity uranium from seawater according to claim 6, characterized in that: In S2, the iron ion solution is one or more of a ferric chloride solution and a ferric sulfate solution, the concentration of the iron ion solution is 0.01 to 1 M in terms of iron ions, the electrodeposition voltage is -0.1 to -0.8 V, and the electrodeposition amount is 3 C / cm 2 ~100C / cm 2 The calcination temperature is 1400-1600°C, and the calcination time is 2-4h.

9. The method for preparing a composite material for extracting low-impurity uranium from seawater according to claim 6, characterized in that: In S3, hydrochloric acid is used for acid leaching, the concentration of the hydrochloric acid is 50-70wt%, and the acid leaching time is 2-6h.

10. An application of a composite material prepared by the preparation method according to any one of claims 1 to 9 for extracting low-impurity uranium from seawater, characterized in that: It is used to electrochemically reduce and extract low-impurity uranium from seawater.

Citation Information

Patent Citations

  • Oxygen evolution electrode material and preparation method and application thereof

    CN117488357A

  • Preparation method of molybdenum oxide-based nanosheet for electrochemical uranium extraction and electrochemical uranium extraction device

    CN117800395A

  • Preparation and application of foamed nickel-loaded polyacid-derived cobalt-molybdenum-nickel sulfide

    CN118256949A

  • Electrochemical Fluorination for Processing of Used Nuclear Fuel

    US20140374272A1